Black Cat. Vol. 07, Time for vengeance - Yabuki, Kentaro (Viz Media, 2007)
Train Heartnet, reformed assassin turned bounty hunter, also known as Black Cat, comes to the aid of a troubled boy seeking revenge for the death of his parents and is forced to confront his own vengeance-laden past. Meanwhile, Rinset forms a shaky new relationship with an old enemy.